Algorithmen und Autonomie Interdisziplinäre Perspektiven auf das Verhältnis von Selbstbestimmung und Datenpraktiken - Verständig, Dan; Kast, Christina; Stricker, Janne; Nürnberger, Andreas (Verlag Barbara Budrich, 2022)
We live in a world of algorithmic sorting and decision-making. Mathematical models curate our social relationships, influence our elections and even decide whether we should go to prison or not. But how much do we really know about code, algorithmic structures and how they work? This book turns to questions of autonomy in the digital age from an interdisciplinary perspective, combining contributions from philosophy, education and cultural studies with computer science.